A model predictive control based MPPT technique for novel DC-DC converter and voltage regulation in DC microgrid - Bhagwan, Kunte Abhijit; Manthati, Udaya Bhasker; Alsaif, Faisal (Frontiers in Energy Research, 2024)
The present work aims to design a system that can extract maximum power using modified Maximum Power Point Tracking technique using novel DC-DC High Gain converter and used this whole system to supply microgrid system using conventional buck converter. This work provided a novel structure by having all the MPPT, boosting the voltage and voltage regulation in DC Microgrid in a single system. When it comes to the Photovoltaic solar system, a high gain converter and extracting maximum power from the PV are the most integral parts. Considering this here, present work will address these things by using a High Gain DC-DC converter that can boost output voltage to ten times the input voltage. Furthermore, the MPPT technique can extract maximum power from the PV panel based on Model Predictive Control, considering its better transient response alongside the conventional incremental conductance method. This MPPT technique can be operated for Fixed and Variable steps operation and compared results are shown with variations of the load. Considering the economics of the system, proposed work will try to reduce the cost of the system by optimizing the sensors two instead of three. Results are presented for different environmental conditions using MATLAB-Simulink and the performance difference between conventional incremental conductance and the presented MPPT technique are shown. After proposing this, the DC voltage regulation for the proposed PV system is done for the existing system and results are shown. During DC voltage regulation, different load conditions and Irradiations are considered by keeping temperature constant. Results were presented using simulation software which shows the latter one has better performance over the first one at different environmental conditions, and results are persistent-the Voltage regulation achieved at different load conditions and irradiations.